Development of Framework for the Best Practices in Maintenance Management of Public Recreation Park: Case Study in Muar Public Recreation Park - Omar, Roshartini; Mustafa, Suryanee Parvin (Journal of Technology Management and Business, 2019)
Public recreation parks are one of the facilities that Local Authorities must provide to the community in a City. In the National Audit Reports, found that most of public facilities in Muar Municipal Council were unsatisfied and had way to be improved where there were some disadvantages that caused the facilities provided to be unprofitable by the public. Among the weaknesses, there are some types of public facilities and their components that are not properly maintained, the provision of public facilities are not fully utilized by the public. The objectives of the study are to understand the maintenance management of public recreation parks in Malaysia, to study the implementation of maintenance management of public recreation park in Muar and to develop the best framework in maintenance management of public recreation park in Muar. Therefore, literature review and qualitative studies were conducted involving 10 respondents of the study by 3 directors from the National Landscape Department and 2 officers from the Muar Municipal Council; and 5 officers from Local Authorities which are Majlis Bandaraya Melaka Bersejarah, Majlis Perbandaran Hang Tuah Jaya, Majlis Bandaraya Shah Alam, Majlis Perbandaran Manjung dan Majlis Perbandaran Klang. Therefore, the data were analyzed by using Content Analysis. The finding shows that, six best practices had been developed within the framework of maintenance management of Muar public recreation park. The practices are the staffing model; goal, standards and design; staff maintenance; develop staff; develop plans; and sustainable maintenance. This study is of interest to the Muar Municipal Council in enhancing the maintenance management of public recreation park in Muar which is of interest to the public.Â Â Keywords: Maintenance, Malaysia, Management, Public Recreation Park, QualitativeÂ